Pengaruh Kemudahan Penggunaan Aplikasi Dan Kepercayaan Pelanggan Terhadap Kepuasan Pelanggan Pada Layanan Gojek Di Jakarta Timur: The Effect of Ease of Use of the Application and Customer Trust on Customer Satisfaction on Gojek Services in East Jakarta - Fadly Ahmad Zarwani; Henny Armaniah (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Abstracts - In the era of digital services such as Gojek, ease of access and user trust are important factors in creating customer satisfaction, but what customers often experience includes application disruptions such as slow loading or errors, tariff discrepancies due to dynamic pricing systems, and difficulties in using certain features. This study aims to analyze the effect of Application Ease of Use and Trust on Gojek Customer Satisfaction in the East Jakarta area. The study uses a quantitative approach with an associative research type. Data collection was carried out through questionnaires distributed to 150 respondents with a purposive sampling technique. The data obtained were analyzed using SPSS version 30 software through various tests, such as validity, reliability, classical assumptions (normality, multicollinearity, heteroscedasticity), and hypothesis testing including t-test, F-test, multiple linear regression, and coefficient of determination. The partial test results show that Application Ease of Use has no significant effect on Customer Satisfaction (1.330 <1.976), while Trust has a significant effect (15.400 >1.976). Meanwhile, the results of the simultaneous test show that both variables together have a significant effect on Customer Satisfaction (Fcount > Ftable, (339.386 > 3.06). This finding confirms that trust has a greater role in determining the level of Gojek customer satisfaction.